Multifunctional Educational Area “Glade of Activity”. Complex Group Work with Children with Autism Spectrum Disorders - Khabarova, S.N.; Esaulkova, I.L. (Autizm i narušenie razvitiâ, 2023)
Objectives. The use and considering of natural environment in the educational work with children with autism spectrum disorders (ASD) can provide a solution to such developmental tasks as physical and social development, social interactions with children and adults, increasing the comfort of the educational environment. The purpose of presented work is to analyze the results of the application of complex psycho-educational work in the setting of the multifunctional educational area "Glade of Activity". Methods. Comprehensive psycho-educational work in the setting of the "Glade of Activity" was carried out in the kindergarten No. 133 in the city of Tyumen. 53 children with ASD took part in the project in the period of 2019- 2023. 74% of children had an intellectual delay, 10% had different intellectual disabilities. Following methods were used: Individual psycho-educational examination for children with autism spectrum disorders (PEP-3), observation method, questionnaires for parents. Results. 92% of subjects had slight positive developmental trend and in 8% of the subjects registered more pronounced positive trend in the development of mental functions, socially acceptable forms of behavior, as well as in the physical development. According to the results of observations and questioning of parents, it is noted that children have become interested in objects of joint activity with teachers and other children. Anxiety outside the group has decreased, independence in choosing the type of activity has increased, involvement in joint activities. There is a decrease in the number and strength of the manifestation of negative reactions. Conclusions. It is planned to include "Glade of Activity" in the comprehensive support system for families raising children of early preschool age with disabilities and different diagnosis. In order to conduct further research, it is planned to develop a system for evaluating the effectiveness of psycho-educational technologies and methods. Актуальность и цель. Применение в работе с детьми с расстройствами аутистического спектра (РАС) естественных природных условий и учет их специфики может обеспечить решение таких задач как физическое и социальное развитие, включение во взаимодействие с детьми и взрослыми, повышение комфорта пребывания в образовательной организации. Цель настоящей работы - анализ промежуточных результатов применения комплексной коррекционной работы педагогов в рамках многофункционального образовательного пространства «Поляна активности». Методы и методики. Комплексная коррекционная работа в рамках пространства «Поляна активности» проводилась на базе детского сада № 133 города Тюмени. С 2019 по 2023 год в проекте принимали участие 53 ребенка с РАС, из них 74% детей имели задержку психического развития, 10% - интеллектуальные нарушения. С целью промежуточной оценки результатов работы использовались следующие методы: Индивидуальное психолого-педагогическое обследование для детей с расстройствами аутистического спектра PEP-3, метод наблюдения, анкетирование родителей. Результаты. В ходе применения комплексной коррекционной работы в 92% случаев наблюдается незначительная положительная динамика, а в 8% случаев более выраженная положительная динамика в развитии психических функций, социально приемлемых форм поведения, а также в физическом развитии детей. По результатам наблюдений и анкетирования родителей, отмечается, что у детей появился интерес к объектам совместной деятельности с педагогами и другими детьми, снизилась тревожность вне помещения группы, повысилась самостоятельность в выборе вида деятельности, включенность в совместную деятельность. Отмечается уменьшение количества и силы проявления негативных реакций. Выводы. Планируется включение «Поляны активности» в систему комплексного сопровождения семей, воспитывающих детей раннего дошкольного возраста с ограниченными возможностями здоровья из различных нозологических групп. С целью проведения дальнейших исследований планируется разработка системы оценки эффективности применения педагогических технологий.